INTEGRATING EDUCATIONAL MANAGEMENT THEORY INTO TEACHING AND LEARNING IMPROVEMENT: EVIDENCE FROM EKITI SUBEB, NIGERIA - Bamidele Folakemi Olabisi; Bamidele Vincent Olawale (PT. ZILLZELL MEDIA PRIMA, 2026)
This study examines the integration of classical, behavioral, systems, contingency, and transformational leadership theories into practical strategies for enhancing teaching and learning outcomes in Ekiti State Universal Basic Education Board (SUBEB) during the 2020–2025 period. The study is motivated by persistent challenges in basic education delivery in Nigeria, including inadequate funding, teacher shortages, infrastructure deficits, and limited community engagement, as well as the gap between educational management theories and their practical application in state-level educational contexts. Through document analysis, theoretical synthesis, and comparative analysis of empirical studies, the research develops a conceptual framework mapping educational management theory to SUBEB strategies for improving teaching and learning outcomes. The findings reveal that SUBEB demonstrates partial application of classical, behavioral, systems, contingency, and transformational leadership theories, with significant gaps in behavioral, systems, and transformational theory implementation. Classical theory provides the foundational framework for organizational structure and accountability, while behavioral theory is partially applied through teacher training and participatory mechanisms. Systems theory informs coordinated planning but is constrained by departmental silos and weak feedback loops. Contingency theory is reflected in contextual adaptation efforts, yet uniform approaches often persist. Transformational and distributed leadership are emerging through leadership training and School-Based Management Committees, but centralized authority limits their full realization. Furthermore, opportunities for enhanced theory-practice integration include fostering a continuous learning culture, improving monitoring and evaluation feedback loops, creating partnerships with external organizations, investing in leadership capacity building, and promoting greater school autonomy and responsibility. These findings suggest that bridging the theory-practice gap requires sustained commitment to organizational learning, capacity development, stakeholder collaboration, and contextual responsiveness to improve educational quality and outcomes in Ekiti State.